Edge of chaos why democracy is failing to deliver economic growth--and how to fix it - Moyo, Dambisa (New York Basic Books, 2018)
Around the world, people who are angry at stagnant wages and growing inequality have rebelled against established governments and turned to political extremes. Liberal democracy, history's greatest engine of growth, now struggles to overcome unprecedented economic headwinds--from aging populations to scarce resources to unsustainable debt burdens. Hobbled by short-term thinking and ideological dogma, democracies risk falling prey to nationalism and protectionism that will deliver declining living standards.
Keywords: Democracy